No unleashed expression without language. (17th February 2023) - Carston, Robyn
Abstract: While the metarepresentational structure of ostensive communication may explain the unleashing of human expression, it neither explains the open-endedness of the thoughts expressed/communicated, nor how the multiply embedded nature of the metarepresentational structure invoked arose. These both require the recursivity of human language, a capacity which must be distinguished from external (public) languages and their use in communication.